Teknik Instruksional Pertanyaan Guru di Tahap Searching for the Theoritical Background of the Driving Question pada Project Based Learning untuk Meningkatkan Skor Pattern Concept Map - Fahma Auliya Dewi; Sri Widoretno; Alanindra Saputra (Universitas Sebelas Maret, 2018)
The aim of the study was to calculate the score pattern on the concept map (CM) of the students by applying instructional instruction technique of teacher in searching for the theoretical background of the driving question on project based learning. The subjects were 32 high school students. The research is a classroom action research with research procedure including: planning to prepare RPP and its completeness, implementation on activity of action, observation to calculate CM pattern score and reflection for next action. Triangulation validation test includes: verification of conformity of CM pattern score and documentation based on expert pattern CM and interview to represent learners' skill structure. Reduction is done to select the completeness of data, presenting the data and drawing conclusions based on the complete data pattern. Data analysis with qualitative descriptive. The results showed that the pattern score based on the expert pattern of CM on precycle was obtained from 40% -60% range with 46,875% of total learner got score below average and 0% above average. Cycle I obtained a score range of 40% -100% with 9.375% showing scores below average and 43.75% above average. Cycle II obtained a score range of 40% -80% with 15.625% indicating scores below average and 12.5% above average, thus the instructional technique question in the searching phase for the theoretical background of the driving question project based learning increases the score pattern CM both individual and classical.